Multi-level artificial dura mater repair stent and preparation method thereof

By designing a multi-level artificial dura repair scaffold, using the multi-drug release and physical barrier function of nanofiber membranes, it solves the problem of difficult to fully deal with the complex pathological environment after brain injury in the existing technology, and achieves effective neural repair and regeneration effects.

CN119746168APending Publication Date: 2025-04-04QINGDAO UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510001980.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to fully respond to complex pathological environments in nerve repair after brain injury, and lacks effective multi-drug release mechanisms and physical barrier functions, which affects the effect of nerve repair.

Method used

A multi-level artificial dura repair scaffold was designed, and the three-layer nanofiber membrane cross-linked by glutaraldehyde was deposited layer by layer. The inner layer was loaded with minocycline and insulin-like growth factor-1, the middle layer was composed of polycaprolactone nanofibers, and the outer layer was composed of polycaprolactone/hyaluronic acid nanofiber membrane, which achieved the timing release of drugs and the physical barrier function.

Benefits of technology

This repair stent can effectively regulate the inflammatory response after brain injury, promote nerve repair and regeneration, prevent cerebrospinal fluid leakage, reduce tissue adhesions, and provide a physical barrier to prevent invasion of non-target cells, thereby significantly improving the repair effect after brain injury.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746168A_ABST
    Figure CN119746168A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical textile materials, and relates to a multi-level artificial dura mater repair scaffold and a preparation method thereof.The main body structure of the repair scaffold is three layers of nanofiber membranes deposited layer by layer and crosslinked through glutaraldehyde, the inner layer is a coaxial nanofiber membrane loaded with minocycline and insulin-like growth factor-1, and the outer layer is a coaxial nanofiber membrane loaded with glutaraldehyde. Wherein the insulin-like growth factor-1 is located in the core layer, and the minocycline is located in the shell layer; the middle layer is a polycaprolactone nanofiber membrane, and the outer layer is a polycaprolactone / hyaluronic acid nanofiber membrane; the inner layer can release minocycline and insulin-like growth factor-1 in a sequential manner, so that the inflammation environment after brain injury can be effectively regulated and controlled, and neural restoration can be promoted; and the outer layer shows an excellent anti-adhesion effect by inhibiting the adhesion and proliferation of fibroblasts, so that the hindrance on nerve regeneration caused by excessive formation of scar tissues is effectively avoided. The middle layer obviously enhances the ability of the stent to prevent leakage of cerebrospinal fluid; and the structural design is exquisite, the preparation method is simple and convenient, and wide market prospects and profound social values are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention belongs to the technical field of biomedical textile materials, and relates to a multi-level artificial dura mater repair scaffold and a preparation method thereof. The main structure of the repair scaffold is composed of three layers, and the inflammatory response after brain injury and the promotion of nerve repair are regulated by the time-sequential release of specific substances (such as minocycline and insulin-like growth factor-1). In addition, the material can effectively prevent cerebrospinal fluid leakage, reduce tissue adhesion, and provide a physical barrier to prevent the invasion of non-target cells. These characteristics are crucial to promoting the recovery of brain injury areas and show the potential for wide application in the field of nerve repair. Background technology:

[0002] Traumatic brain injury is caused by external forces such as blunt trauma, external impact or penetrating trauma to the head, and causes brain function damage and severe physical, cognitive and emotional disorders. Traumatic brain injury can be divided into two stages: primary brain injury and secondary brain injury. Primary injury is difficult to reverse and has strong resistance to treatment; although it cannot be eradicated, timely medical intervention can slow its progression and lay the foundation for the prevention of secondary injury. Secondary injury gradually appears after primary injury and involves complex physiological and biochemical cascade reactions. Fortunately, there is a critical time window in this stage. By taking targeted medical measures, secondary injury can be effectively reduced, thereby improving the long-term clinical treatment effect. Therefore, the treatment of traumatic brain injury needs to focus on timely intervention of primary injury and active prevention of secondary injury, in order to minimize the impact of brain injury on the body.

[0003] The dura mater is located between the skull and brain tissue and acts as a natural barrier. Defects in the dura mater can lead to cerebrospinal fluid leakage, infection invasion, and increased risk of meningitis, so timely repair is required to maintain the integrity of the anatomical structure and promote meningeal healing. After the dura mater is damaged, fibroblasts are activated to participate in wound healing, but if the secretion of extracellular matrix is ​​unbalanced, it may lead to tissue adhesion, fibrosis, and scar tissue formation, hindering nerve repair. At the same time, neuroinflammation in the area of ​​brain damage activates macrophages, releases inflammatory mediators, inhibits the repair and regeneration of damaged nerves, and further aggravates nerve damage. In addition, brain injury is often accompanied by adverse environments such as hypoxia and oxidative stress. These factors work together to aggravate the severity and complexity of nerve damage.

[0004] With the rapid development of the field of biomedical materials, more and more biomedical scaffolds have been invented and used to treat various diseases, showing great value and potential in the treatment of diseases that damage the nervous system. Among them, electrospinning technology has attracted much attention due to its simple operation, strong repeatability, suitability for large-scale production, low cost of raw materials, and rich variety of spinning materials. This technology can make full use of natural proteins, degradable polymers and their complexes, greatly broadening its scope of application. Through electrospinning technology, nanofibers with diverse structures can be accurately constructed. These fibers are not only morphologically controllable, but also can be endowed with specific biological functions according to treatment needs. Therefore, electrospun nanofiber membranes have become one of the important biomaterials for the treatment of nervous system diseases due to their unique structure and biological activity.

[0005] Recent studies have shown that artificial dura mater prepared by electrospinning technology has been used for repair after brain injury. However, the existing dura mater has a relatively single function and can usually only promote neural repair through a simple single drug release mode, which cannot fully cope with the complex pathological environment after brain injury. Therefore, it is particularly important to develop a multi-layered nanofiber dura mater repair scaffold. This multi-layered scaffold can achieve the precise release of multiple drugs, better simulate the physiological environment, promote neural repair and regeneration, and thus effectively cope with the complex pathological changes after brain injury.

[0006] So far, no research reports have been found on the use of static spinning technology combined with emulsion electrospinning technology and electrospun nanofiber membranes prepared from drugs such as hyaluronic acid and minocycline for the repair of damaged nerves after brain injury. Summary of the invention:

[0007] The purpose of the present invention is to solve the shortcomings of the prior art and provide a multifunctional multi-layered artificial dura mater repair scaffold and a preparation method thereof. The designed multi-layered dura mater biomaterial has good biocompatibility and degradability, promotes the healing and repair of brain injury areas, and has important applications in the field of neural repair after brain injury.

[0008] In order to achieve the above object, the present invention provides a multi-level artificial dura mater repair scaffold, the main structure of the repair scaffold is a three-layer nanofiber membrane deposited layer by layer and cross-linked by glutaraldehyde, the inner layer is composed of a coaxial nanofiber membrane loaded with minocycline and insulin-like growth factor-1, wherein insulin-like growth factor-1 is located in the core layer and minocycline is located in the shell layer; the middle layer is composed of a polycaprolactone nanofiber membrane, and polycaprolactone, due to its hydrophobic properties and good mechanical strength, can effectively prevent the leakage of cerebrospinal fluid after brain injury, maintain a stable environment of brain tissue, and provide support for nerve repair; the outer layer is composed of a polycaprolactone / hyaluronic acid nanofiber membrane, which can inhibit the excessive proliferation of fibroblasts, effectively prevent tissue adhesion and scar formation, and protect the normal growth of new nerve fibers. In addition, the topological characteristics of the multi-level structure itself also play a physical barrier role, preventing the invasion of other cells and ensuring the smooth progress of the nerve repair process. The multifunctional multi-level nanofiber dura mater repair scaffold of the present invention can effectively promote the repair process after brain injury in many aspects through its unique structural design and material properties, and provide patients with better therapeutic effects.

[0009] The artificial dura mater repair scaffold of the present invention can release minocycline and insulin-like growth factor-1 in a sequential manner, which can effectively regulate the inflammatory environment after brain injury and promote nerve repair. Specifically, the early and large-scale release of minocycline can quickly relieve acute inflammation, while the long-term and continuous release of insulin-like growth factor-1 is conducive to the repair and regeneration of nerve cells.

[0010] The present invention also provides a method for preparing the multi-level artificial dura mater repair scaffold, which specifically comprises the following steps:

[0011] (1) Preparing the outer layer of the stent: a hyaluronic acid solution and a polycaprolactone solution are mixed, and then a sorbitan oleate solution is added, the mixture is blended and dissolved uniformly to obtain a polycaprolactone / hyaluronic acid spinning solution, and then a polycaprolactone / hyaluronic acid nanofiber membrane is prepared by single-nozzle electrospinning as the outer layer of the stent;

[0012] (2) Preparing the middle layer of the stent: using a polycaprolactone solution as a spinning solution and the polycaprolactone / hyaluronic acid nanofiber membrane obtained in step (1) as a receiving substrate, preparing a polycaprolactone nanofiber membrane as the middle layer of the stent by single-nozzle electrospinning;

[0013] (3) Preparing the inner layer of the stent: after mixing the polycaprolactone solution and the insulin-like growth factor-1 / bovine serum albumin solution, add the sorbitan oleate solution, blend and dissolve evenly, and obtain an insulin-like growth factor-1 / bovine serum albumin / polycaprolactone emulsion mixed spinning solution as the core layer solution; dissolving gelatin, polycaprolactone and minocycline in an organic solvent to obtain a gelatin / polycaprolactone / minocycline spinning solution as the shell layer solution; and then using the polycaprolactone nanofiber membrane obtained in step (2) as a receiving substrate, preparing a dual coaxial structure of insulin-like growth factor-1 / bovine serum albumin / polycaprolactone / gelatin / polycaprolactone / minocycline nanofiber membrane by a double nozzle coaxial electrospinning technology as the inner layer of the stent;

[0014] (4) Preparation of a multi-layer artificial dura mater repair scaffold: The three layers of fiber membranes are deposited layer by layer, and then cross-linked with glutaraldehyde to obtain a multi-layer artificial dura mater repair scaffold.

[0015] In the step (1), the hyaluronic acid solution is prepared by dissolving hyaluronic acid in a solvent, the solvent is formic acid, and the mass volume ratio of hyaluronic acid to formic acid is (18-22) mg:1 mL; the polycaprolactone solution is prepared by dissolving polycaprolactone in an organic solvent, the organic solvent is hexafluoroisopropanol, and the mass volume ratio of polycaprolactone to hexafluoroisopropanol is (280-320) mg:3 mL.

[0016] In the step (1), the hyaluronic acid solution and the polycaprolactone solution are mixed uniformly at a volume ratio of 1:10, and then a sorbitan oleate solution of 1% of the volume of the polycaprolactone solution is added, and the mixture is placed in a magnetic stirrer and stirred and mixed uniformly to obtain a polycaprolactone / hyaluronic acid spinning solution.

[0017] The polycaprolactone / hyaluronic acid spinning solution obtained in the step (1) is used to prepare a polycaprolactone / hyaluronic acid nanofiber membrane by single-nozzle electrospinning; at this time, the electrospinning parameters are: positive voltage of 10-15kV, negative voltage of 3kV, flow rate of 3mL / h, duration of 40 minutes, and receiving distance of 20cm.

[0018] The polycaprolactone solution in step (2) is prepared by dissolving polycaprolactone in an organic solvent, wherein the organic solvent is hexafluoroisopropanol, and the mass volume ratio of polycaprolactone to hexafluoroisopropanol is (280-320) mg:3 mL.

[0019] The polycaprolactone spinning solution obtained in step (2) is used to prepare a polycaprolactone nanofiber membrane by single-nozzle electrospinning. The electrospinning parameters are: positive voltage of 10-15 kV, negative voltage of 3 kV, flow rate of 3 mL / h, duration of 40 minutes, and receiving distance of 20 cm.

[0020] In the step (3), an emulsion mixed spinning solution of insulin-like growth factor-1 / bovine serum albumin / polycaprolactone is prepared, and the polycaprolactone solution is obtained by dissolving polycaprolactone in an organic solvent 1, the organic solvent 1 is dichloromethane, and the mass volume ratio of polycaprolactone to dichloromethane is (230-250) mg:3 mL. The insulin-like growth factor-1 / bovine serum albumin solution is obtained by dissolving insulin-like growth factor-1 and bovine serum albumin in a solvent, the solvent is double distilled water, and the mass volume ratio of insulin-like growth factor-1, bovine serum albumin and double distilled water is 1 mg:1 mg:1 mL.

[0021] The insulin-like growth factor-1 / bovine serum albumin solution and the polycaprolactone solution obtained in step (3) are mixed evenly in a volume ratio of 1:20, and then a sorbitan oleate solution with a volume ratio of 1% of the polycaprolactone solution is added, and the mixture is placed in a magnetic stirrer and stirred and mixed evenly to obtain an insulin-like growth factor-1 / bovine serum albumin / polycaprolactone emulsion mixed spinning solution as the core layer solution.

[0022] In the step (3), the organic solvent in which gelatin, polycaprolactone and minocycline are dissolved is hexafluoroisopropanol, and the mass volume ratio of gelatin, polycaprolactone, minocycline and hexafluoroisopropanol is (260-300) mg: (111-128) mg: 5 mg: 5 mL. The mixture is placed in a magnetic stirrer and stirred and mixed to obtain a gelatin / polycaprolactone / minocycline spinning solution as a shell solution.

[0023] In the step (3), the emulsion mixed spinning solution of insulin-like growth factor-1 / bovine serum albumin / polycaprolactone is used as the core solution and the gelatin / polycaprolactone / minocycline spinning solution is used as the shell solution, and the insulin-like growth factor-1 / bovine serum albumin / polycaprolactone / gelatin / polycaprolactone / minocycline nanofiber membrane with a double coaxial structure is prepared by coaxial electrospinning technology with a double nozzle and deposited on the polycaprolactone nanofiber membrane. At this time, the electrospinning parameters are: positive voltage of 10-15kV, negative voltage of 3kV, core layer flow rate of 0.5mL / h, shell layer flow rate of 0.5mL / h, duration of 70 minutes, and receiving distance of 15cm.

[0024] In the step (4), the three-layer scaffold is deposited layer by layer and placed in a glutaraldehyde fumigation pot for cross-linking for 2-6 hours to obtain a multi-layer artificial dura mater repair scaffold.

[0025] The main structure of the repair stent of the present invention is three layers of nanofibers, and the inner layer combines coaxial electrospinning technology and emulsion electrospinning technology to successfully prepare dual coaxial nanofibers capable of sequentially releasing minocycline and insulin-like growth factor-1. By accurately adjusting the spinning parameters and material ratios, the repair stent can achieve a dual release mode of two drugs, release the corresponding drugs according to different periods after brain injury, and effectively promote nerve repair. In the acute phase of brain injury, minocycline is rapidly released, effectively controlling the inflammatory response, prompting brain BV2 cells to change from the pro-inflammatory M1 phenotype to the anti-inflammatory M2 phenotype, thereby reducing further damage to nerve cells by inflammation, and promoting the repair of damaged nerves. The long-acting sustained release mechanism of insulin-like growth factor-1 not only helps to alleviate acute injuries, but also counteracts potential secondary nerve damage, providing continuous repair and protection. The middle layer is composed of polycaprolactone nanofibers, which use their excellent mechanical strength and hydrophobicity to prevent cerebrospinal fluid leakage and maintain a stable environment for brain tissue. The outer layer is made of polycaprolactone / hyaluronic acid composite nanofibers, which have the effect of inhibiting excessive proliferation of fibroblasts and reducing postoperative adhesions. The physical barrier of the repair scaffold can prevent the invasion of other cells and ensure that the nerve repair process is not disturbed. Overall, this multi-level artificial dura mater repair scaffold has excellent biocompatibility and degradability, and can also adjust the type and release rate of sustained-release components according to clinical needs, showing significant application potential in the treatment of meningeal defects related to traumatic brain injury.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The inner layer of the present invention adopts advanced spinning technology and material ratio control to achieve a dual release mechanism of drugs. This design not only avoids the inconvenience of frequent drug replacement during traditional treatment, but also can accurately deliver corresponding drugs according to the needs of different brain injury stages. In particular, the inner layer is preloaded with the anti-inflammatory drug minocycline and insulin-like growth factor-1 that promotes nerve regeneration. Through the combined action of these drugs, the local immune response in the brain injury area is effectively regulated, accelerating the repair process of nerve cells. This method of customized drug delivery according to different stages of brain injury recovery greatly improves the treatment effect.

[0028] (2) The outer layer of the present invention exhibits an excellent anti-adhesion effect by inhibiting the adhesion and excessive proliferation of fibroblasts, effectively avoiding the obstruction of nerve regeneration caused by excessive scar tissue formation. The middle layer, with its excellent mechanical strength and hydrophobicity, significantly enhances the ability of the stent to prevent cerebrospinal fluid leakage, which is crucial for maintaining a stable physiological environment of brain tissue and creating favorable conditions for nerve repair.

[0029] (3) The artificial dura mater repair scaffold of the present invention exhibits a strong physical barrier effect, which can effectively prevent the invasion of foreign cells, ensure the cleanliness and safety of the nerve repair area, and provide an ideal microenvironment for nerve regeneration.

[0030] (4) The present invention is highly flexible and customizable. It can flexibly select different drugs to be loaded and adjust the drug release rate and the structural configuration of the three layers of meninges for different degrees of brain injury diseases to meet the personalized treatment needs of different patients and promote the healing and recovery of brain injury areas. It has shown significant application potential in the field of neural repair after brain injury and has great application prospects in the field of multi-level biomedical biomaterials for the brain. The repair stent of the present invention has good biocompatibility and degradability, and its structural design is exquisite and the preparation method is simple, which provides the possibility for large-scale production and application, indicating broad market prospects and far-reaching social value. Description of the drawings:

[0031] Figure 1 It is a schematic diagram of the multi-layer nanofiber dura mater repair scaffold involved in the present invention.

[0032] Figure 2 This is a real picture of the multi-layer artificial dura mater repair stent involved in the present invention, wherein A is a photo of the outer layer of the stent, B is a photo of the middle layer of the stent, C is a photo of the inner layer of the stent, and D is a cross-sectional photo of the multi-layer artificial dura mater repair stent.

[0033] Figure 3 These are scanning electron microscope (SEM) images of the multi-layer artificial dura mater repair scaffold involved in the present invention, wherein A is the SEM image of the outer layer of the scaffold, B is the SEM image of the middle layer of the scaffold, C is the SEM image of the inner layer of the scaffold, and D is the SEM image of the entire cross-section of the repair scaffold.

[0034] Figure 4 The sustained-release curves of the nanofiber membrane in the inner layer of the repair stent involved in the present invention sequentially release two drugs, A is the sustained-release curve of minocycline (MH), and B is the sustained-release curve of rhodamine (RB) replacing insulin-like growth factor-1 (IGF-1).

[0035] Figure 5 The present invention relates to the effect of the inner layer nanofiber membrane of the repair stent on the viability of SH-SY5Y cells after acute oxidative stress treatment.

[0036] Figure 6 The figure shows the effect of the inner layer nanofiber membrane of the repair stent involved in the present invention on the axon growth of SH-SY5Y cells after acute oxidative stress treatment, wherein A is a statistical graph of average axon length, and B is a statistical graph of the longest axon length.

[0037] Figure 7This is the effect of the inner layer nanofiber membrane of the repair stent involved in the present invention on the phenotypic polarization of BV2 cells, wherein A is the fluorescence expression intensity of iNOS, and B is the fluorescence expression intensity of Arg-1.

[0038] Figure 8 The figure shows the anti-adhesion ability of the outer nanofiber membrane of the repair stent involved in the present invention. A is the cell viability of fibroblasts cultured on the outer nanofiber membrane of the stent for 1, 3, and 5 days, B is the fluorescence quantitative result of the proliferation of fibroblasts on the outer nanofiber membrane of the stent, and C is the fluorescence staining image of the proliferation of fibroblasts on the outer nanofiber membrane.

[0039] Fig. 9 The test results of the anti-leakage ability of the multi-level artificial dura mater repair stent of the present invention are shown in Figure 1, where AH are pressure-free fluorescent droplet experiments. From left to right, from top to bottom, A is 0 minutes (no rhodamine solution is added), B is 0 minutes after adding rhodamine solution, C is 10 minutes, D is 20 minutes, E is 30 minutes, F is 40 minutes, G is the front side of the membrane after 50 minutes, and H is the back side of the membrane at 50 minutes. IL is a fluorescent droplet penetration experiment of the multi-level artificial dura mater repair stent, I is 5 minutes, J is 10 minutes, K is 30 minutes, and L is 60 minutes (the yellow dotted line indicates the lower surface of the multi-level artificial dura mater repair stent). Specific implementation method:

[0040] The present invention will be further described below through specific embodiments in conjunction with the accompanying drawings.

[0041] Embodiment 1:

[0042] This embodiment relates to a method for preparing a multi-level artificial dura mater repair scaffold, and the specific steps include:

[0043] (1) Preparation of the outer layer of the stent: Weigh 0.3 g of polycaprolactone (PCL) and dissolve it in 3 mL of hexafluoroisopropanol (HFIP), stir it with a magnetic stirrer for 12 hours, and stir it evenly to obtain a PCL solution with a concentration of 0.1 g / mL; weigh 0.02 g of hyaluronic acid (HA) and dissolve it in 1 mL of formic acid, stir it with a magnetic stirrer for 12 hours, and stir it evenly to obtain a HA solution with a concentration of 0.02 g / mL. Add 0.3 mL of HA solution to 3 mL of PCL solution, and then add 0.03 mL of sorbitan oleate (span-80) solution, stir it thoroughly for 12 hours to obtain PCL / HA spinning solution, and use existing electrospinning equipment to prepare PCL / HA random nanofiber membrane, which is the outer layer of the stent (referred to as PCL / HA-NDM); the electrospinning parameters are: positive voltage of 10-15 kV, negative voltage of 3 kV, flow rate of 3 mL / h, duration of 40 minutes, and receiving distance of 20 cm;

[0044] (2) Preparation of the middle layer of the stent:

[0045] 0.3 g of PCL was weighed and dissolved in 3 mL of HFIP, and stirred evenly with a magnetic stirrer for 12 hours to obtain a PCL solution with a concentration of 0.1 g / mL as a spinning solution; an existing electrospinning device was used to prepare a PCL random nanofiber membrane, which was the middle layer of the scaffold (denoted as PCL-NDM); the electrospinning parameters were: positive voltage of 10-15 kV, negative voltage of 3 KV, flow rate of 3 mL / h, duration of 40 minutes, and receiving distance of 20 cm;

[0046] (3) Preparation of the inner layer of the stent:

[0047] 0.24 g of PCL was weighed and dissolved in 3 mL of dichloromethane (DCM), and stirred with a magnetic stirrer for 3 hours to obtain a PCL solution with a concentration of 0.08 g / mL; 0.15 mL of an insulin-like growth factor-1 / bovine serum albumin (IGF-1 / BSA) aqueous solution with a growth factor concentration of 1 mg / mL was prepared (insulin-like growth factor-1 and bovine serum albumin were dissolved in double distilled water, and the mass volume ratio of insulin-like growth factor-1, bovine serum albumin and double distilled water was 1 mg:1 mg:1 mL); 3 mL of the PCL solution prepared above and 0.15 mL The IGF / BSA aqueous solutions were mixed, and then 0.03 mL of span-80 (sorbitan oleate) solution was added, and a magnetic stirrer was used for 6 hours to stir evenly to obtain an IGF-1 / BSA / PCL emulsion mixed spinning solution as the core layer solution; 0.28 g of gelatin (Gel), 0.12 g of PCL and 5 mg of minocycline (MH) were accurately weighed using an electronic balance and dissolved in 5 mL of HFIP, and a magnetic stirrer was used for 6 hours to stir evenly to obtain the Gel / PCL / MH spinning solution as the shell layer solution; a dual-nozzle coaxial electrospinning technology was used to prepare a dual-coaxial structured IGF-1 / BSA / PCL / Gel / PCL / MH nanofiber membrane as the inner layer of the scaffold (denoted as MH+IGF-NDM). The electrospinning parameters were: positive voltage 10-15 kV, negative voltage 3 kV, core layer flow rate 0.5 mL / h, shell layer flow rate 0.5 mL / h, duration 70 min, receiving distance 15 cm;

[0048] (4) Preparation of multi-layered nanofiber dura mater repair scaffold: The above three-layer scaffold was deposited layer by layer, and then placed in a glutaraldehyde fumigation pot for cross-linking for 4 hours to obtain a multi-layered artificial dura mater repair scaffold (MH+IGF-MDNM).

[0049] In this embodiment, a digital camera was used to photograph the outer layer, middle layer, inner layer and cross section of the prepared stent as well as the multi-level artificial dura mater repair stent. Figure 2A, 2B, 2C and 2D. The results showed that each layer of the artificial dura mater repair scaffold was relatively smooth, without obvious droplets and particles, and no obvious stratification was observed in cross-sectional observation.

[0050] In this example, the outer layer, middle layer, inner layer and cross section of the prepared stent as well as the multi-layer artificial dura mater repair stent were photographed by SEM for further characterization. Figure 3 A, 3B, 3C and 3D. The results showed that the fibers of each layer of the scaffold were interlaced, the diameters were relatively evenly distributed, no obvious stratification was observed in the cross section, and the layers were tightly combined.

[0051] Embodiment 2:

[0052] The present embodiment relates to a method for preparing a multi-layer artificial dura mater repair scaffold, which is different from that of Example 1 in that: the HA solution in step (1) is obtained by dissolving 0.018 g of hyaluronic acid (HA) in 1 mL of formic acid; the polycaprolactone solution in step (3) is obtained by dissolving 0.23 g of polycaprolactone in 3 mL of dichloromethane; the shell solution is obtained by dissolving 0.30 g of gelatin (Gel), 0.111 g of PCL and 5 mg of minocycline (MH) in 5 mL of HFIP; the other steps are the same, and finally a multi-layer artificial dura mater repair scaffold is prepared.

[0053] Embodiment 3:

[0054] The present embodiment relates to a method for preparing a multi-layer artificial dura mater repair scaffold, which is different from that of Example 1 in that: the HA solution in step (1) is obtained by dissolving 0.022 g of hyaluronic acid (HA) in 1 mL of formic acid; the polycaprolactone solution in step (3) is obtained by dissolving 0.25 g of polycaprolactone in 3 mL of dichloromethane; the shell solution is obtained by dissolving 0.26 g of gelatin (Gel), 0.128 g of PCL and 5 mg of minocycline (MH) in 5 mL of HFIP; the other steps are the same, and finally a multi-layer artificial dura mater repair scaffold is prepared.

[0055] Embodiment 4:

[0056] This example is an in vitro release experiment of bioactive molecules and drugs from the inner layer IGF-1 / BSA / PCL / Gel / PCL / MH nanofiber membrane of the stent prepared in Example 1. First, the inner fiber membrane was prepared according to step (3) of Example 1, and glutaraldehyde was used to cross-link for 4 hours to detect the release of MH. Each group of 50 mg of the inner fiber membrane of the artificial dura mater repair stent was added to a centrifuge tube containing 5 mL of phosphate buffered saline (PBS), placed in a 37°C constant temperature shaker, and shaken at 120 rpm; the sustained-release solution was taken out at 1 hour, 2 hours, 3 hours, 4 hours, 12 hours, 1 day, and 3 days, and its absorbance at 360 nm was measured to detect the release of minocycline. After each sampling, an equal volume of fresh PBS solution was immediately added to the centrifuge tube.

[0057] According to step (3) of Example 1, rhodamine B (RB) was used as the model load (1 mg / mL) of IGF-1 to prepare the inner layer nanofiber membrane of the stent, and glutaraldehyde was used for cross-linking for 4 hours to reflect the release of IGF-1 by detecting RB. 50 mg of the inner layer nanofiber membrane of the stent was weighed in each group and added to a centrifuge tube containing 5 mL of phosphate buffered saline (PBS), placed in a 37°C constant temperature shaker, and shaken at 120 rpm. The sustained-release solution was taken out at 1 day, 3 days, 5 days, 7 days, 10 days, 14 days, 20 days, 27 days, 35 days and 42 days, and its absorbance at 554 nm was measured to detect the release of RB and thus understand the release of IGF-1. After each sampling, an equal volume of fresh PBS solution was immediately added to the centrifuge tube.

[0058] Preparation method of the inner layer nanofiber membrane of the stent for detecting MH release: accurately weigh 0.24 g of PCL with an electronic balance and dissolve it in 3 mL of DCM, stir it evenly with a magnetic stirrer for 3 hours to obtain a PCL solution with a concentration of 0.08 g / mL; then prepare 0.15 mL of an IGF-1 / BSA aqueous solution with a concentration of 1 mg / mL; mix the PCL solution and the BSA aqueous solution prepared above, add 0.03 mL of a span-80 solution, stir it evenly with a magnetic stirrer for 6 hours to obtain a BSA / PCL emulsion mixed spinning solution as a core layer solution; use an electronic balance Accurately weigh 0.28g of Gel, 0.12g of PCL and 5mg of MH and dissolve them in 5mL of HFIP. Use a magnetic stirrer for 6 hours to stir evenly, and the obtained Gel / PCL / MH spinning solution is used as the shell solution. The double-nozzle coaxial electrospinning technology is used to prepare a double-coaxial structure of BSA / PCL / Gel / PCL / MH nanofiber membrane to obtain the inner layer of the stent. The electrospinning parameters are: positive voltage of 10-15kV, negative voltage of 3kV, core layer flow rate of 0.5mL / h, shell layer flow rate of 0.5mL / h, duration of 70 minutes, and receiving distance of 15cm.

[0059] Preparation method of the inner layer nanofiber membrane of the stent for detecting the release of IGF-1: 0.24 g of PCL was accurately weighed with an electronic balance and dissolved in 3 mL of DCM, and stirred evenly with a magnetic stirrer for 3 hours to obtain a PCL solution with a concentration of 0.08 g / mL; then 0.15 mL of RB / BSA aqueous solution with a RB concentration of 1 mg / mL was prepared (Rhodamine-B and bovine serum albumin were dissolved in double distilled water, and the mass volume ratio of Rhodamine-B, bovine serum albumin and double distilled water was 1 mg:1 m g:1mL); the PCL solution and RB / BSA aqueous solution prepared above were mixed, and then 0.03mL of span-80 solution was added, and a magnetic stirrer was used for 6 hours to stir evenly to obtain a RB / BSA / PCL emulsion mixed spinning solution as a core layer solution; 0.28g of Gel, 0.12g of PCL and 5mg of MH were accurately weighed with an electronic balance and dissolved in 5mL of HFIP, and a magnetic stirrer was used for 6 hours to stir evenly to obtain a Gel / PCL / MH spinning solution as a shell layer solution. The inner layer of the stent was obtained by preparing a double coaxial structure of RB / BSA / PCL / Gel / PCL / MH nanofiber membrane using a double nozzle coaxial electrospinning technology. The electrospinning parameters are: positive voltage of 10-15kV, negative voltage of 3kV, core layer flow rate of 0.5mL / h, shell layer flow rate of 0.5mL / h, duration of 70 minutes, and receiving distance of 15cm.

[0060] The release behavior experimental results of the drug MH and the model load RB carried by the inner layer of the stent prepared by the method of the present invention are as follows: Figure 4 As shown. Figure 4 A shows that MH is released in large quantities in the early stage and continues until the third day, when a large amount of MH is released from the scaffold. This early rapid release mode can effectively alleviate the damage to nerves caused by early acute inflammation after traumatic brain injury, and reduce the inflammatory response by regulating the inflammatory environment at the site of injury. At the same time, RB was selected as a model substance of IGF-1 to detect its sustained release behavior. Figure 4 B It can be seen that the release curve of RB shows a trend of sustained release, and the slow release can be sustained up to 49 days. Within the first 5 days, the cumulative release of RB from the inner nanofiber membrane reached 43.97%. From the 5th day to the 42nd day, RB still showed a continuous and gradually slow release trend. On the 42nd day, the cumulative release exceeded 90%, meeting the needs of long-term sustained release. The long-term sustained release of IGF-1 not only has a good repair effect on damaged nerve cells in the acute phase after brain injury, but also has a repair and protective effect on long-term secondary nerve damage. Through this dual release mechanism of the drug, the inner nanofiber membrane of the stent can effectively regulate the local immune response in the brain injury area, accelerate the repair process of nerve cells, and significantly improve the treatment effect.

[0061] Embodiment 5:

[0062] This example is to study the neurorepair effect of the prepared inner layer nanofibers of the scaffold on SH-SY5Y cells after the oxidative stress injury experiment. The specific experimental steps are: SH-SY5Y cells (cell density is 6000 / well) are inoculated in a 24-well plate, and cultured for 24 hours with complete medium (the complete medium is DMEM high-glucose medium containing 10% fetal bovine serum and 1% penicillin-streptomycin), and oxidative stress injury experiments are performed on SH-SY5Y cells after they are attached to the wall. After 1 day of intervention, different inner layer nanofiber membranes are co-cultured with SH-SY5Y cells through Transwell chambers for 1, 3, and 5 days, that is, 1, 3, and 5 days after oxidative stress injury treatment, and the proliferation of SH-SY5Y cells is detected by the cck-8 kit; and 3 days after oxidative stress injury treatment, the axon growth of SH-SY5Y cells is detected by the axon staining kit.

[0063] The experiment was divided into 5 groups, namely, control group, NDM group, MH-NDM group, IGF-NDM group and MH+IGF-NDM group. The control group was pure cell culture without adding any nanofiber membrane; the NDM group used NDM membrane, that is, an inner nanofiber membrane without any drug; the MH-NDM group used MH-NDM membrane, that is, an inner nanofiber membrane loaded with MH; the IGF-NDM group used IGF-NDM membrane, that is, an inner nanofiber membrane loaded with IGF-1; the MH+IGF-NDM group used an inner nanofiber membrane loaded with MH and IGF-1, that is, the IGF-1 / BSA / PCL / Gel / PCL / MH nanofiber membrane prepared in step (3) of Example 1 was cross-linked with glutaraldehyde for 4 hours to sterilize it.

[0064] The preparation method of the NDM membrane is different from step (3) of Example 1 in that MH and IGF-1 are not added, the other steps are the same, and the prepared nanofiber membrane is cross-linked with glutaraldehyde for 4 hours. The preparation method of the MH-NDM membrane is different from step (3) of Example 1 in that MH is not added, the other steps are the same, and the prepared nanofiber membrane is cross-linked with glutaraldehyde for 4 hours.

[0065] The preparation method of the IGF-NDM membrane is different from step (3) of Example 1 in that IGF-1 is not added, and the other steps are the same, and the prepared nanofiber membrane is further cross-linked with glutaraldehyde for 4 hours.

[0066] The oxidative stress experimental method is specifically as follows: the culture medium in the well plate is removed, and 0.4 mL of a complete culture medium solution containing 200 μM H2O2 is added to each well for 24 hours to simulate an oxidative stress state.

[0067] The method of co-culturing the inner layer nanofiber membrane of the scaffold with SH-SY5Y cells using a Transwell chamber is specifically as follows: SH-SY5Y cells are planted in a 24-well plate, a Transwell chamber is placed after the cells adhere to the wall, the sterilized nanofiber membrane is placed above the Transwell chamber, 1 mL of culture medium is added to each well so that the top and bottom of the Transwell chamber can be connected by the culture medium, and the nanofiber membrane above the chamber can repair the SH-SY5Y cells by releasing bioactive molecules or drugs in the culture medium.

[0068] The specific method for detecting the proliferation of SH-SY5Y cells using the CCK-8 kit is as follows: on the 1st, 3rd, and 5th days of culture, the Transwell chamber is moved to a new 24-well plate, the culture medium in the well plate is aspirated, 0.4 mL of the prepared 10% CCK-8 solution is added to each well, protected from light, placed in a 37°C cell culture incubator for 1.5 hours, and then taken out, and the CCK-8 solution in the 24-well plate is added to the 96-well plate with a pipette, 100 μL per well, and the absorbance of each well at 450 nm is detected by an enzyme marker.

[0069] The 10% cck-8 solution is a complete culture medium containing 10% cck-8 stock solution.

[0070] The specific method for detecting the axon growth of SH-SY5Y cells by the axon staining kit is as follows: on the third day of culture, the Transwell chamber is moved to a new 24-well plate, the culture medium in the well plate is removed, and 0.4 mL of the prepared axon fluorescent dye is added to each well, protected from light, and placed in a 37°C cell culture incubator for 30 minutes before being taken out. The axon fluorescent dye is aspirated with a pipette, rinsed 3 times with Dulbecco's phosphate buffered saline (D-PBS), 0.4 mL of background inhibitor is added to each well, and the axon growth of the cells is observed with an upright fluorescence microscope after aspirating 0.4 mL of background inhibitor with a pipette.

[0071] The axon fluorescent staining solution is prepared by mixing the cell membrane staining solution and the cell viability indicator in the axon staining kit with D-PBS at a volume ratio of 1:1000.

[0072] The background suppression dye solution was prepared by mixing the background suppression dye in the axon staining kit with D-PBS at a volume ratio of 1:100.

[0073] This example studies the repair effect of different scaffold inner layer nanofiber membranes on SH-SY5Y cells after oxidative stress experiment. The results of cell proliferation and cell axon growth are as follows: Figure 5 and Figure 6 shown.

[0074] from Figure 5 It can be seen that on the first day, the cell viability of the MH+IGF-NDM group and the IGF-NDM group was slightly higher than that of the MH-NDM group, the NDM group, and the Control group. Due to the continuous repair and protection of nerves by IGF-1, on the fifth day after injury, the cell viability of the MH+IGF-NDM group and the IGF-NDM group was significantly higher than that of the other groups, indicating that the continuous release of IGF-1 by the prepared artificial dura mater helps promote the repair of nerves caused by oxidative stress in the acute phase after brain injury.

[0075] from Figure 6 It can be seen that the average axon length and the longest axon length of the neurons of SH-SY5Y cells intervened by MH+IGF-NDM group and IGF-NDM group were significantly higher than those of MH-NDM group, NDM group and Control group, indicating that the continuous release of IGF-1 by the prepared artificial dura mater helps promote the neural repair of neural damage caused by oxidative stress after TBI.

[0076] Embodiment 6:

[0077] This embodiment relates to the effect of the inner layer nanofiber membrane of the scaffold prepared in Example 1 on the phenotypic polarization of BV2 cells after the inflammatory model induction experiment. The specific experimental steps are: BV2 cells (cell density is 5000 / well) were inoculated in a 24-well plate, cultured with complete medium for 24 hours, and after the BV2 cells adhered to the wall, they were subjected to the inflammatory model induction experiment intervention for 1 day, and different inner layer nanofiber membranes were co-cultured with BV2 cells through Transwell chambers for 3 days, that is, 3 days after the inflammatory model induction treatment, and the phenotypic polarization of BV2 was detected by iNOS and Arg-1 immunofluorescence staining.

[0078] The complete culture medium is a DMEM high-glucose culture medium containing 10% fetal bovine serum and 1% penicillin-streptomycin.

[0079] The experimental method for inducing the inflammation model is specifically as follows: the culture medium in the well plate is aspirated, and 0.4 mL of 1 μg / mL lipopolysaccharide (LPS) solution culture medium is added to each well for 24 hours to promote the polarization of BV2 cells from the M0 phenotype to the pro-inflammatory M1 phenotype.

[0080] The experiment was divided into five groups, with a pure blank group without any treatment as the control group (Control group), a group that was only induced by LPS and not subjected to any material intervention as the LPS group, an NDM group using an inner nanofiber membrane without any drug, an MH-NDM group using an inner nanofiber membrane loaded with MH, and an MH group using MH, the amount of MH used in the MH group being the same as that used in the MH-NDM group. The preparation methods of the NDM group and the MH-NDM group were the same as those in Example 5.

[0081] The method of co-culturing the nanofiber membrane and BV2 cells using the Transwell chamber is specifically as follows: BV2 cells are plated in a 24-well plate, a Transwell chamber is placed after the cells adhere to the wall, the sterilized nanofiber membrane is placed above the Transwell chamber, 1 mL of culture medium is added to each well so that the top and bottom of the Transwell chamber can be connected by the culture medium, and the nanofiber membrane above the chamber can regulate the phenotypic polarization of BV2 cells by releasing drugs in the culture medium.

[0082] The specific method for detecting the phenotypic polarization of BV2 by iNOS and Arg-1 immunofluorescence staining is:

[0083] (1) After co-culturing different inner nanofiber dura mater with BV2 cells via Transwell chamber for 3 days, the culture medium in the well plate was removed and the well plate was washed 3 times with PBS;

[0084] (2) Fix the cells with 0.2 mL / well of 4% tissue cell fixative at room temperature for 30 minutes, remove the tissue cell fixative, and then wash three times with PBS;

[0085] (3) Permeabilize with 0.25% triton X-100 aqueous solution (0.2 mL / well) at room temperature for 5 min, remove the triton X-100 solution, and then wash with PBS three times;

[0086] (4) Block with 0.2 mL / well of 1% bovine serum albumin (BSA) aqueous solution for 60 min, remove the BSA solution and wash with PBS three times;

[0087] (5) iNOS / Arg-1 was mixed with 1% BSA aqueous solution at a volume ratio of 1:250, and then 200 μL of the mixture was added to each well and kept in a refrigerator at 4 degrees overnight;

[0088] (6) The next day, take the plate out of the refrigerator, remove the primary antibody dye, and wash it twice with PBS, 10 minutes each time;

[0089] (7) Prepare the secondary antibody dye corresponding to iNOS and a 1% BSA aqueous solution at a volume ratio of 1:1000, prepare the secondary antibody dye corresponding to Arg-1 and a 1% BSA aqueous solution at a volume ratio of 1:1000; then add them to the wells corresponding to iNOS / Arg-1, incubate at room temperature in the dark for 60 minutes. Remove the secondary antibody dye and wash twice with PBS, 10 minutes each time;

[0090] (8) Seal the slides with a sealing medium containing DAPI, observe and photograph under a positive microscope at the same fluorescence intensity, and use Image J software to calculate the fluorescence expression intensity of different groups at the same fluorescence intensity.

[0091] This example studies the effect of the inner nanofiber dura mater scaffold on the phenotypic polarization of BV2 cells after the inflammatory model induction experiment. iNOS is commonly used as a marker for BV2 cells with M1 pro-inflammatory phenotype, and Arg-1 is commonly used as a marker for BV2 cells with M2 anti-inflammatory phenotype. The results are shown in Figure 7 As shown. Figure 7 It can be seen that compared with the LPS group and the NDM group, the expression levels of iNOS in the MH-NDM group and the MH group were significantly reduced; at the same time, compared with the control group, the LPS group and the NDM group, the expression levels of Arg-1 in the MH-NDM group and the MH group were significantly increased. These results indicate that the inner nanofiber dura mater scaffold can effectively regulate the phenotypic polarization of BV2 cells by releasing minocycline (MH), promoting its transformation from the pro-inflammatory M1 phenotype to the anti-inflammatory M2 phenotype. This regulatory effect helps to improve the inflammatory environment after brain injury and provide a more favorable microenvironment for the repair of nerve damage.

[0092] Embodiment 7:

[0093] This embodiment relates to the anti-adhesion effect of the outer nanofiber membrane of the stent prepared in Example 1 on mouse embryonic fibroblasts (NIH3T3 cells) after the oxidative stress injury experiment. The specific steps are: first, use biological glue to paste the PCL-NDM or PCL / HA-NDM prepared in Example 1 on a glass slide, use a pure blank glass slide group as a control group, and sterilize the aforementioned glass slides and materials and place them in a 24-well plate. Fibroblasts were inoculated in a 24-well plate (cell density was 6000 cells / well), cultured with complete medium, and different nanofiber membranes were co-cultured with NIH3T3 cells for 1, 3, and 5 days, respectively, and the proliferation of fibroblasts was detected by the cck-8 kit. At the same time, according to the above steps, a 24-well plate with NIH3T3 cells cultured on different nanofiber membranes was plated again. On the third day of culture, it was taken out and Ki67 stained to evaluate the effect of different nanofiber membranes on fibroblast proliferation.

[0094] The complete culture medium is a DMEM high-glucose culture medium containing 10% fetal bovine serum and 1% penicillin-streptomycin.

[0095] The experiment was divided into three groups: a pure pore plate group without any nanofiber membrane as the control group (Control group), a PCL-NDM group using the PCL-NDM in the middle layer of the scaffold prepared in step (2) of Example 1, and a PCL / HA-NDM group using the PCL / HA-NDM in the outer layer of the scaffold prepared in step (1) of Example 1.

[0096] The specific method for detecting the proliferation of fibroblasts using the CCK-8 kit is as follows: on the 1st, 3rd, and 5th days of culture, the culture medium in the well plate is aspirated, and 0.4 mL of the prepared 10% CCK-8 solution is added to each well. The well is protected from light and placed in a 37°C cell culture incubator for 1.5 hours before being taken out. The CCK-8 solution in the 24-well plate is added to the 96-well plate with a pipette, 100 μL per well, and the absorbance of each well at 450 nm is detected with an enzyme marker.

[0097] The 10% cck-8 solution is a complete culture medium containing 10% cck-8 stock solution.

[0098] The specific method for detecting the proliferation of fibroblasts by Ki67 immunofluorescence staining is:

[0099] (1) After co-culturing different nanofiber dura maters with NIH3T3 cells for 3 days, the culture medium in the well plate was removed and the well plate was washed three times with PBS;

[0100] (2) Fix the cells with 0.2 mL / well of 4% tissue cell fixative at room temperature for 30 minutes, remove the tissue cell fixative, and then wash three times with PBS;

[0101] (3) Permeabilize with 0.25% Triton X-100 aqueous solution (0.2 mL / well) at room temperature for 5 minutes, remove the Triton X-100 solution, and then wash with PBS three times;

[0102] (4) Block with 0.2 mL / well of 5% BSA aqueous solution for 30 min, remove the BSA solution and wash with PBS three times;

[0103] (5) Ki67 and 5% BSA aqueous solution were mixed at a volume ratio of 1:200, and then 200 μL of the mixture was added to each well and kept in a refrigerator at 4 degrees overnight. The primary antibody dye was removed and the wells were washed twice with PBS for 20 minutes each time.

[0104] (6) Prepare a secondary antibody dye corresponding to Ki67 and a 5% BSA aqueous solution at a volume ratio of 1:1000, then add it to the corresponding wells and incubate in the dark at room temperature for 60 minutes. Remove the secondary antibody dye and wash twice with PBS for 10 minutes each time;

[0105] (7) Seal the slides with a sealing medium containing DAPI, observe and photograph under a positive microscope at the same fluorescence intensity, and use Image J software to calculate the fluorescence expression intensity of different groups at the same fluorescence intensity.

[0106] During wound healing, fibroblasts are activated, which enhances the secretion of cytoplasmic matrix, promoting wound healing and tissue regeneration. Balanced secretion of cytoplasmic matrix is ​​essential for wound healing, because the accumulation of excessive cytoplasmic matrix can lead to the development of tissue adhesion and cause tissue fibrosis and scar tissue formation. This example studies the effect of different nanofiber membranes on fibroblast proliferation, and the results are as follows Figure 8 As shown. Figure 8 As can be seen from A, fibroblasts were inoculated on PCL-NDM and PCL / HA-NDM for culture, and the cell viability of fibroblasts was measured after 1, 3, and 5 days of cell culture. The cell viability increased from day 1 to day 5. However, compared with the Control group and the PCL-NDM group, the cell viability of the PCL / HA-NDM group was significantly reduced, indicating that the PCL / HA-NDM group could inhibit the excessive proliferation of fibroblasts relative to the other two groups. Figure 8 BC shows that compared with the Control group and PCL-NDM group, the expression of Ki67 in the PCL / HA-NDM group was significantly reduced, which is consistent with the previous cell viability test results. This shows that PCL / HA-NDM can effectively inhibit the excessive proliferation of fibroblasts, reduce excessive deposition of extracellular matrix, avoid tissue adhesion and fibrosis, and create a favorable microenvironment for nerve repair.

[0107] Embodiment 8:

[0108] This example involves the anti-leakage ability test of the multi-layer artificial dura mater repair stent and the stent outer layer, stent middle layer and stent inner layer prepared in Example 1. The anti-leakage ability of the repair stent is tested by a pressureless droplet penetration test and a fluorescent dye penetration test.

[0109] The experiment was divided into four groups: PCL / HA-NDM group, which tested the anti-permeability of PCL / HA-NDM in the outer layer of the scaffold; PCL-NDM group, which tested the anti-permeability of PCL-NDM in the middle layer of the scaffold; MH+IGF-DNM group, which tested the anti-permeability of MH+IGF-DNM in the inner layer of the scaffold; and MH+IGF-MDNM group, which tested the anti-permeability of MH+IGF-MDNM, a multi-layer artificial dura mater repair scaffold. The inner layer MH+IGF-DNM of the scaffold and the multi-layer artificial dura mater repair scaffold MH+IGF-MDNM needed to be cross-linked with glutaraldehyde for 4 hours before the experiment.

[0110] The specific method of the pressureless droplet penetration experiment is as follows: the above-mentioned different nanofiber membranes are cut into circles with a diameter of 14 mm and fixed on a clean surface. Then, 5 μL of rhodamine solution (concentration 0.25 mg / mL) is dripped onto different membranes. After 10 minutes, 20 minutes, 30 minutes, 40 minutes, and 50 minutes of dripping the rhodamine solution, observe whether the rhodamine droplets penetrate from one side of the material to the other side to qualitatively evaluate its anti-leakage performance.

[0111] The specific method of the fluorescent dye penetration experiment is as follows: the multi-layer artificial dura mater repair scaffold (MH+IGF-MDNM) is cut into a circle with a diameter of 14 mm and fixed on a clean surface. Then, 10 μL of rhodamine solution (concentration 0.25 mg / mL) is dripped onto the scaffold. After 5, 10, 30 and 60 minutes of dripping the rhodamine solution, an upright fluorescence microscope is used to observe whether the rhodamine droplets penetrate from one side of the material to the other side to further evaluate its anti-leakage performance.

[0112] Dura mater defects caused by brain injury may cause leakage of cerebrospinal fluid, thereby affecting the process of nerve repair. This example studies the anti-leakage ability of the multi-layer artificial dura mater repair scaffold and each layer of the scaffold. The results are as follows Fig. 9 As shown. Fig. 9 AH shows that in the pressureless droplet penetration experiment, the rhodamine solution of the MH+IGF-NDM group and the PCL / HA-NDM group spread out immediately, and the MH+IGF-MDNM group was dripped from the inner layer, and the same phenomenon as the MH+IGF-NDM group was observed. The PCL-NDM group has strong hydrophobicity, and when the rhodamine solution is dripped on it, droplets are formed on the PCL-NDM surface. Over time, it was observed at the 50th minute that the red droplets on the surface of the PCL-NDM group showed a lighter color and a reduced volume. In addition, the leakage-proof performance of each group of membranes was detected by observing the color changes on the lower surface. At the 50th minute, there was no red impregnation on the lower surface of the PCL-NDM group and the MH+IGF-MDNM group, while there was obvious red impregnation on the lower surface of the MH+IGF-NDM group and the PCL / HA-NDM group. Therefore, the PCL-NDM prepared by the present invention can effectively block the penetration of rhodamine solution droplets, and can play a good anti-leakage role when loaded into the finished membrane. On this basis, the anti-leakage performance of MH+IGF-MDNM was further evaluated by fluorescent dye penetration experiment. Fig. 9 It can be seen in the IL that at different time points, the red fluorescence could not penetrate the entire layer of the membrane to reach the lower surface of the MH+IGF-MDNM, indicating that the prepared MH+IGF-MDNM effectively blocked the leakage of the droplets and played a good anti-leakage effect, which is consistent with the previous experimental results and provides favorable conditions for nerve repair.

Claims

1. A multi-level artificial dura mater repair stent, characterized in that: The main structure of the repair stent is a three-layer nanofiber membrane deposited layer by layer and cross-linked by glutaraldehyde. The inner layer is a coaxial nanofiber membrane loaded with anti-inflammatory drugs and growth factors, in which insulin-like growth factor-1 is located in the core layer and minocycline is located in the shell layer; the middle layer is a polycaprolactone nanofiber membrane, and the outer layer is a polycaprolactone / hyaluronic acid nanofiber membrane.

2. A method for preparing a multi-level artificial dura mater repair scaffold, characterized in that: The specific steps include: (1) Preparing the outer layer of the stent: mixing a hyaluronic acid solution and a polycaprolactone solution, adding a sorbitan oleate solution, blending and dissolving the mixture evenly, obtaining a polycaprolactone / hyaluronic acid spinning solution, and then preparing a polycaprolactone / hyaluronic acid nanofiber membrane by single-nozzle electrospinning, which is the outer layer of the stent; (2) Preparation of the middle layer of the stent: using a polycaprolactone solution as the spinning solution, a polycaprolactone nanofiber membrane is prepared by single-nozzle electrospinning, which is the middle layer of the stent; (3) Preparing the inner layer of the stent: after mixing the polycaprolactone solution and the insulin-like growth factor-1 / bovine serum albumin solution, add the sorbitan oleate solution, blend and dissolve evenly, and obtain an insulin-like growth factor-1 / bovine serum albumin / polycaprolactone emulsion mixed spinning solution as the core layer solution; dissolving gelatin, polycaprolactone and minocycline in an organic solvent and dissolving evenly to obtain a gelatin / polycaprolactone / minocycline spinning solution as the shell layer solution; preparing a double coaxial structure of insulin-like growth factor-1 / bovine serum albumin / polycaprolactone / gelatin / polycaprolactone / minocycline nanofiber membrane by a double nozzle coaxial electrospinning technology, which is the inner layer of the stent; (4) Preparation of a multi-layer artificial dura mater repair scaffold: The three-layer scaffold is deposited layer by layer, and then cross-linked with glutaraldehyde to obtain a multi-layer artificial dura mater repair scaffold.

3. The method for preparing the multi-level artificial dura mater repair scaffold according to claim 2, characterized in that: The hyaluronic acid solution in step (1) is prepared by dissolving hyaluronic acid in a solvent, the solvent is formic acid, and the mass volume ratio of hyaluronic acid to formic acid is (18-22) mg:1 mL; the polycaprolactone solution in steps (1) and (2) is prepared by dissolving polycaprolactone in an organic solvent, the organic solvent is hexafluoroisopropanol, and the mass volume ratio of polycaprolactone to hexafluoroisopropanol is (280-320) mg:3 mL; the hyaluronic acid solution and the polycaprolactone solution are uniformly mixed at a volume ratio of 1:10; and the amount of sorbitan oleate added is 1% of the volume of the polycaprolactone solution.

4. The method for preparing the multi-level nanofiber dura mater material repair scaffold according to claim 2, characterized in that: The electrospinning parameters of step (1) and step (2) are: positive voltage of 10-15 kV, negative voltage of 3 kV, flow rate of 3 mL / h, duration of 40 minutes, and receiving distance of 20 cm.

5. The method for preparing the multi-level nanofiber dura mater material repair scaffold according to claim 2, characterized in that: The polycaprolactone solution in step (3) is obtained by dissolving polycaprolactone in an organic solvent 1, wherein the organic solvent 1 is dichloromethane, and the mass volume ratio of polycaprolactone to dichloromethane is (230-250) mg:3 mL; the insulin-like growth factor-1 / bovine serum albumin solution is obtained by dissolving insulin-like growth factor-1 and bovine serum albumin in a solvent, wherein the solvent is double distilled water, and the mass volume ratio of insulin-like growth factor-1, bovine serum albumin and double distilled water is 1 mg:1 mg:1 mL.

6. The method for preparing the multi-level nanofiber dura mater material repair scaffold according to claim 2, characterized in that: In step (3), the insulin-like growth factor-1 / bovine serum albumin solution and the polycaprolactone solution are mixed evenly at a volume ratio of 1:20, and then sorbitan oleate is added at 1% of the volume of the polycaprolactone solution.

7. The method for preparing the multi-level nanofiber dura mater material repair scaffold according to claim 2, characterized in that: In step (3), the organic solvent in which gelatin, polycaprolactone and minocycline are dissolved is hexafluoroisopropanol, and the mass volume ratio of gelatin, polycaprolactone, minocycline and hexafluoroisopropanol is (260-300) mg:(111-128) mg:5 mg:5 mL.

8. The method for preparing the multi-level nanofiber dura mater material repair scaffold according to claim 2, characterized in that: The electrospinning parameters in step (3) are: positive voltage of 10-15 kV, negative voltage of 3 kV, core layer flow rate of 0.5 mL / h, shell layer flow rate of 0.5 mL / h, duration of 70 minutes, and receiving distance of 15 cm.

9. The method for preparing the multi-level nanofiber dura mater repair scaffold according to claim 2, characterized in that: The cross-linking time in step (4) is 2-6 hours.

10. An application of the multi-layer artificial dura mater repair scaffold as claimed in claim 1 in biological tissue engineering, characterized in that: The multi-layered artificial dura mater repair scaffold releases minocycline and insulin-like growth factor-1 in a timely manner. The scaffold effectively controls the inflammatory response and promotes nerve repair through the rapid release of minocycline in the acute phase; the long-acting sustained release mechanism of insulin-like growth factor-1 not only helps to alleviate acute injuries, but also can combat potential secondary nerve damage and provide repair and protection; in addition, the scaffold also has the ability to prevent leakage, inhibit fibroblast proliferation to reduce adhesion, and act as a barrier to external cell invasion to prevent the entry of other cells from affecting the nerve repair process.

Citation Information

Cited By

  • MXene-based artificial dura mater as well as preparation method and application thereof

    CN121177573A

  • Intervertebral disc fibrous ring repairing material, stent and application of intervertebral disc fibrous ring repairing material and stent

    CN121401491A

  • Multi-level degradable artificial meninx repair stent and preparation method thereof

    CN121819014A